Löpmagsförskjutning hos mjölkkor : en besättningsutredning för att identifiera riskfaktorer för metaboliska störningar - Olsson, Lars (SLU/Dept. of Ruminant Medicine and Veterinary Epidemiology, 2004)
The purpose of this study was to find possible explanations to why the studied herd had an increased incidence of abomasal displacements. The incidence of abomasal displacement in the herd was three times higher than the incidence of an average Swedish herd. The cows in this study were fed a total mixed ration. The different parameters studied were: energy content in food, nutritional content in food, body condition scoring, concomitant other diseases, and blood parameters of glucose, fructosamine, cholesterol, insulin, betahydroxybutyrat and free fatty acids. The author's suggestions to decrease the problems are to decrease the energy content in the TMR to lower the cows' body condition scores in the dry period and changing the content in the TMR to increase the amount of NDF and adding structure in the form of chopped straw.